Enteroparasitoses em crianças de 0 a 6 anos de creches municipais de Rio Verde-GO e sua interface com o meio ambiente - Zaiden, Marilúcia Fonseca (2006)
This descriptive-analytical study aimed to evaluate the interface between the incidence of enteroparasites in children aged 0 to 6 years in four municipal daycare centers in Rio Verde-GO and the environment, based on the incidence of enteric protozoa and helminths in children, by selected daycare center, and the relationship of the indexes found with predisposing factors. Fecal samples were collected from 276 children, who were subjected to two laboratory diagnostic methods, namely: Hoffman's method, Pons and Janer and Faust's method. To support the results obtained from this collection, a form was also used, which was applied to mothers and / or guardians of the children, containing the child's identification and the factors predisposing to worms. The results showed a higher incidence of children in the age group of four, female, coming from the very neighborhood where the daycare center was located, whose parents, in their majority, had incomplete elementary schooling (71.0%). The results of the coprological exams showed that of the total number of female children, 42.3% were positive and, of the total number of male children, 37.7% also presented positive results, without any significant difference being detected between the results. Regarding the species of enteroparasites, the data showed a higher incidence of the protozoan Giardia lamblia (21.4%) and Entamoeba coli (12.0%). In third place comes the association between Giardia lamblia and Entamoeba coli (3.3%) and in fourth place Hymenolepis nana with 1.4%. When looking for the distribution of coprological results by daycare center surveyed, there was a higher incidence of Giardia lamblia in daycare center 1 (Central) with 36.7%, followed by daycare center 2 (27.8%), daycare center 3 (21.2%) and daycare center 4 (13.6%). The incidence of Entamoeba coli behaved in the opposite way, being higher in daycare center 4 (16.0%), followed by 3 (12.1%), 2 (11.1%) and 1 (2.0 %). The results of the association of Giardia lamblia and Entamoeba coli showed a higher incidence in daycare center 2 (5.5%) followed by 3 (4.6%) and 4 (3.2%). These results combined with the data set resulting from the survey of the factors predisposing to enteroparasitoses allowed a range of reflections on the results, reinforcing the fact that enteroparasitoses represent a serious public health problem and that they are related to the risk factors that individuals are exposed during life, especially children.